Early Diagnosis of Subclinical Atherosclerosis in Asymptomatic Type 2 Diabetic Normotensive Menopausal Women: A Global Pulse Wave Velocity Study - Maiello, Maria; Amati, Francesca; Caretto, Pierpaolo; Ciccone, Marco Matteo; Palmiero, Pasquale (International Journal of Angiology, 2024)
Arterial stiffness serves as a cardiovascular disease marker, aiding in the early identification of high-risk patients. We aimed to evaluate the prevalence of arterial stiffness, measured by global pulse wave velocity (gPWV), among diabetic normotensive menopausal women (DPMW) and its correlation with levels of glycosylated hemoglobin (HbA1c). We recruited 641 consecutive DPMW diagnosed with type 2 diabetes over 5 years. The control group (CG) consisted of 300 normotensive, normoglycemic menopausal women. Normal gPWV was defined as a velocity ≤7.1 m/s. We enrolled 641 DPMW with a mean age of 57 ± 12 years. The CG comprised 300 normotensive, normoglycemic postmenopausal women with a mean age of 56 ± 4 years. Among DPMW, 29 (4.5%) exhibited increased gPWV compared with 4 (1.3%) in the CG (p < 0.01). Of the 225 (35.1%) DPMW with HbA1c > 7.5%, 23 (10.2%) had increased gPWV. In contrast, among the 416 (64.9%) DPMW with HbA1c < 7.5%, only 6 (1.4%) had increased gPWV (p < 0.0001). Electrocardiographic (ECG) abnormalities were detected in 208 (32.4%) DPMW, with 11 (5.3%) of them exhibiting increased gPWV (p = 0.6). There was a higher prevalence of increased gPWV in asymptomatic normotensive DPMW, with a significant association between increased gPWV and elevated HbA1c levels. However, there was no correlation between increased gPWV and abnormal ECG findings, despite ECG being the sole test recommended by current guidelines for all diabetic patients. Early detection of elevated HbA1c levels and increased gPWV may identify asymptomatic DPMW at higher cardiovascular risk, highlighting the inadequacy of a simple ECG in assessing cardiovascular risk in this population.
Keywords: menopausal women; normotensive; diabetes; atherosclerosis; early diagnosis; pulse wave velocity; arterial stiffness